Pengaruh Tanah Timbunan Terhadap Daya Dukung Pondasi Telapak (Square Footing) - Beni Deni Sitompul; Irwan Irwan; Kamaluddin Lubis (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2021)
The lower structure of a building construction consists of a foundation and a layer of soil to support the load of the upper construction. The condition of the soil under the structure is closely related to the behavior of the soil itself when it receives loads, for example failures that occur in the sub-grade of the embankment foundation, namely the foundation soil is too soft so that the carrying capacity of the soil to withstand the load of the embankment is small, as a result the settlement that occurs is too large. So the soil layer under the structure must be strong, stable, safe, so that it does not decrease, does not break, because it will be difficult to repair a foundation system. The purpose of this study was to determine the effect of embankment soil on a footing foundation and how much settlement was caused to the foundation. The Plaxis D2 V20 method is a finite element method that aims to analyze and design the geotechnical field. Soil samples were taken at the hospital. Wulan Windi, Medan City, using manual tools. The embankment soil investigation aims to determine the nature and characteristics of the embankment soil carried out at the Civil Engineering Laboratory of the Medan Area University and the Medan State Polytechnic laboratory. The results of the soil embankment research showed that the density of soil (Gs) = 2.63 gr, wet soil volume weight (γb) = 14.8512 kN/m3, dry soil volume weight (γd) = 0.3236 kN/m3, soil permeability ( K)= 12,929 cm/hour, shear stress (φ) = 23,610 . Soil cohesion (c) = 0.057 kg/cm2, Modulus of elasticity (E) = 2400 kN/m2 . Then from the results of the running plaxis, the deformation is 0.1601 meters, while that of the Steinbrenner method, the resulting decrease is 0.1232 m. which causes the plate footing of the tread foundation to fracture. The stress that occurs in the soil is 0.012 kN/m2 and from the analysis results obtained a safety factor of 1 (one).